168k views
2 votes
What is 2(x -3) = 7 (x+24)

User Shanaka
by
5.3k points

2 Answers

2 votes

Answer:

x=34.8

Explanation:

First thing you gotta do is distribute the parenthesis.

2(x-3)= 2x-6

7(x+24)=7x+168

2x-6=7x+168

Next, we simplify our equation and subtract 6 from both sides, along with subtracting 7x from both sides.

2x-6=7x+168

+6 +6

2x=7x+174

-7x -7x

-5x=174

Our final step is to divide both sides by -5.


(-5x=174)/(-5)

x=34.8

User Thomas PEDOT
by
6.0k points
4 votes

Answer:

x = -34.8

Explanation:

solve the equation

2(x-3)

= 2x - 6

7(x + 24 )

= 7x + 168

put the equation together

2x - 6 = 7x + 168

now make x subject of formula:

2x - 7x = 168 +6

-5x = 174

x = 174/ -5

x = -34.8

User Joseph Siefers
by
5.1k points